2007
DOI: 10.1016/j.ejphar.2006.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear isobologram and superadditive withdrawal from cocaine:cannabinoid combinations in planarians

Abstract: Elucidation of interactions between drugs used in polydrug abuse is especially important. However, the necessary experimental conditions for precise quantitative analysis are difficult to establish. Because withdrawal effects of cocaine and the cannabinoid receptor agonist WIN 55212-2 are easily quantified in planarians, demonstration of synergistic effects (P < 0.01) of certain ratios of this combination was possible. This synergy, here analyzed with the latest (nonlinear) isobolographic methodology, is now q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The present findings are part of a larger investigation of planarian withdrawal from abused drugs (e.g., Raffa and Valdez, 2001;Raffa et al, 2003;Umeda et al, 2004;Raffa and Desai, 2005;Rawls et al, 2006) including combinations of drugs (Raffa et al, 2006(Raffa et al, , 2007. Planarians are useful for such studies because of the simplicity of the model and the existing literature on the behavioral responses to a variety of neurotransmitters and selective ligands (e.g., Needleman, 1967;Carolei et al, 1975;Algeri et al, 1983;Venturini et al, 1989;Palladini et al, 1996;Passarelli et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
“…The present findings are part of a larger investigation of planarian withdrawal from abused drugs (e.g., Raffa and Valdez, 2001;Raffa et al, 2003;Umeda et al, 2004;Raffa and Desai, 2005;Rawls et al, 2006) including combinations of drugs (Raffa et al, 2006(Raffa et al, , 2007. Planarians are useful for such studies because of the simplicity of the model and the existing literature on the behavioral responses to a variety of neurotransmitters and selective ligands (e.g., Needleman, 1967;Carolei et al, 1975;Algeri et al, 1983;Venturini et al, 1989;Palladini et al, 1996;Passarelli et al, 1999).…”
Section: Discussionmentioning
confidence: 93%
“…The researchers established a nonlinear isobologram and found that the combination of cocaine and cannabinoids produced a strong withdrawal symptoms (Raffa et al, 2007). Detailed isobolographic analysis indicated additivity at EC10 to EC30 and antagonism at low levels (EC-NOEC to EC5) for the compound to 3-benzylidene camphor, benzophenone-1, and benzophenone-2 (Kunz and Karl, 2009).…”
Section: Application Of Isobologram Analysis To Evaluate Drug Interacmentioning
confidence: 99%
“…The nonlinear isobologram demonstrated that the combination of cocaine and cannabinoid has synergistic effects on planarians (Raffa et al, 2007). When the ratio of rotenone to Cinnamomum cassia Presl oil is 1:35, the synergistic effect of rotenone on the third instar larvae is good for Spodoptera litura (Li et al, 2017; Wen et al, 2013).…”
Section: Application Of Isobologram Analysis To Evaluate Drug Interacmentioning
confidence: 99%
“…When confined to just the single term isobole , with at least two substances, the number of publications dropped to 59. When the list of 38 is viewed against the five drug combinations that resulted in the most hospital admissions (shown in Table ), we get the numbers of publications shown in Table that deals with these toxic combinations of interest. Here, we see a rather large number of publications involving alcohol with the several groups indicated.…”
Section: Commentmentioning
confidence: 99%